2015
DOI: 10.1200/jco.2015.33.18_suppl.lba5002
|View full text |Cite
|
Sign up to set email alerts
|

A phase III protocol of androgen suppression (AS) and 3DCRT/IMRT versus AS and 3DCRT/IMRT followed by chemotherapy (CT) with docetaxel and prednisone for localized, high-risk prostate cancer (RTOG 0521).

Abstract: LBA5002 Background: High-risk, localized prostate cancer (PCa) patients have a relatively poor prognosis. We hypothesized that the addition of adjuvant docetaxel and prednisone to long-term (24 month) AS and radiation therapy (RT) would improve overall survival (OS). Methods: RTOG 0521 opened December 2005 and closed August 2009 with targeted accrual of 600 cases. It was designed to detect improvement in 4-year OS from 86% to 93% with a 51% hazard reduction (HR = 0.49). Under a 0.05 1-sided type I error and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 0 publications
2
49
0
1
Order By: Relevance
“…Cancer (RTOG 0521) trial 4 randomized 562 men with highrisk localized prostate cancer treated with radiation and two years of androgen deprivation therapy (ADT), with and without the addition of adjuvant docetaxel (six cycles) and prednisone starting four weeks after radiation. The four-year OS was 93% for the docetaxel arm versus 89% in the standard group (p = 0.04, HR 0.70).…”
Section: Phase III Protocol Of Androgen Suppression (As) and 3dctr/ Imentioning
confidence: 99%
“…Cancer (RTOG 0521) trial 4 randomized 562 men with highrisk localized prostate cancer treated with radiation and two years of androgen deprivation therapy (ADT), with and without the addition of adjuvant docetaxel (six cycles) and prednisone starting four weeks after radiation. The four-year OS was 93% for the docetaxel arm versus 89% in the standard group (p = 0.04, HR 0.70).…”
Section: Phase III Protocol Of Androgen Suppression (As) and 3dctr/ Imentioning
confidence: 99%
“…Taxanes have been and continue to be evaluated in the non-metastatic setting of prostate cancer across several disease states. [42][43][44][45][46][47][48][49][50] Given the absence of a definitively demonstrated overall survival benefit, treating this patient population should remain investigational at this time.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study contrast those of the three previously reported post-radiation adjuvant studies that all showed an improvement in recurrence-free survival and immature OS estimates. [17][18][19] Other than the local treatment modality used, the only major differences between this study and the other four is the lack of ADT used in the Scandinavian post-surgical study. More studies are needed to fully understand the role (if any) of chemotherapy in this population.…”
mentioning
confidence: 99%